Pedicularis raghvendrae (Orobanchaceae), a new species from Sikkim Himalaya, India - Garg, Arti; Singh, Rajeev Kumar; Kholia, Bhupendra Singh (Phytotaxa, 2020)
Pedicularis raghvendrae, is described as a new species from the Sikkim Himalaya, India. The new species belongs to Pedicularis series Furfurae and is closely related to P. pantlingii, but differs by its shorter size, smaller leaves, smaller, villous, 4-toothed calyx, shorter calyx teeth, corolla white with light pinkish tinge, galea deflexed opposite to the midlobe of labium, midlobe of labium broadly elliptic-ovate, apex acute-obtuse, base distinctly stipitate, stamens inserted at base of corolla tube and filaments longer, all glabrous.